Seismic evidence for a slab tear at the Puerto Rico Trench. Issue 6 (14th June 2013) - Meighan, Hallie E.; Pulliam, Jay; ten Brink, Uri; López‐Venegas, Alberto M.
Abstract: [1] The fore‐arc region of the northeast Caribbean plate north of Puerto Rico and the Virgin Islands has been the site of numerous seismic swarms since at least 1976. A 6 month deployment of five ocean bottom seismographs recorded two such tightly clustered swarms, along with additional events. Joint analyses of the ocean bottom seismographs and land‐based seismic data reveal that the swarms are located at depths of 50–150 km. Focal mechanism solutions, found by jointly fitting P wave first‐motion polarities and S / P amplitude ratios, indicate that the broadly distributed events outside the swarm generally have strike‐ and dip‐slip mechanisms at depths of 50–100 km, while events at depths of 100–150 km have oblique mechanisms. A stress inversion reveals two distinct stress regimes: The slab segment east of 65°W longitude is dominated by trench‐normal tensile stresses at shallower depths (50–100 km) and by trench‐parallel tensile stresses at deeper depths (100–150 km), whereas the slab segment west of 65°W longitude has tensile stresses that are consistently trench normal throughout the depth range at which events were observed (50–100 km). The simple stress pattern in the western segment implies relatively straightforward subduction of an unimpeded slab, while the stress pattern observed in the eastern segment, shallow trench‐normal tension and deeper trench‐normal compression, is consistent with flexure of the slab due to rollback. These results support the hypothesis that the subducting North American plate is tearing at or near these swarms. The 35 year record of seismic swarms at this location and the recent increase in seismicity suggest that the tear is still propagating. Key Points: Ocean‐bottom seismometer deployment increased hypocenter geometric constraints Stress axes aligned with extension from flexure of subducting N.Amer. plate Two stress regimes indicates different processes thus slabtear located inbetween